2010
DOI: 10.1007/s12194-010-0099-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of optimal viewing size for detecting nodular ground-glass opacity on high-resolution computed tomography with cine-mode display

Abstract: We evaluated the effect of the displayed image sizes on observers' ability to detect nodular ground-glass opacity (n-GGO) on CT and investigated the optimal viewing size for soft-copy reading at CT screening for lung cancer. A total of 46 patients' high-resolution computed tomography (HRCT) images (22 patients with one GGO; 24 without GGO) were displayed on a monochromatic liquid crystal display monitor at a resolution of 1,200 × 1,600. HRCT was presented on the screen with cine-mode display. We compared two v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The magnitude of the difference in the JAFROC FOM is roughly comparable to the difference found by Gur et al (2006). However, Yamaguchi et al (2011) found much greater, statistically significant differences between small and large images. Although the size of the images used in their study is comparable to the size of the images used in our experiment, a possible reason for this difference might be the use of different types of stimulus material.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The magnitude of the difference in the JAFROC FOM is roughly comparable to the difference found by Gur et al (2006). However, Yamaguchi et al (2011) found much greater, statistically significant differences between small and large images. Although the size of the images used in their study is comparable to the size of the images used in our experiment, a possible reason for this difference might be the use of different types of stimulus material.…”
Section: Discussionsupporting
confidence: 69%
“…The empirical evidence with regard to the influence of image size on performance is mixed: Several studies that used tile-mode CT, meaning that slices were presented next to each other on a light box (Schaefer at al., 1992;Seltzer, Judy, Feldman, Scarff, & Jacobson, 1998), or single radiographs (Bessho, Yamaguchi, Fujita, & Azuma, 2009) showed disadvantages for small images (12 × 12 cm to 15 × 15 cm) compared to large images (30 × 30 cm), as measured by the area under the receiver operating characteristic (ROC) curve. However, two studies that were conducted to ascertain performance relative to image size differences have shown slight advantages for small images (Gur et al, 2006;Yamaguchi et al, 2011). In these experiments, stackmode CT images were used, meaning that slices were presented individually on the monitor and radiologists scrolled through them at their own pace.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the participants nonetheless rated the large images as more comfortable to interpret. Yamaguchi et al 4 also found a statistically significant advantage for small images (13 × 13 cm) compared with enlarged ones (30 × 30 cm) regarding the area under the ROC curve when identifying nodular ground-glass opacity on CT displayed in cine mode. Although Yamaguchi et al did not report a systematic evaluation of comfort, they mentioned that all seven interpreters strongly indicated that the original image size of 13 × 13 cm was easier to interpret.…”
Section: Introductionmentioning
confidence: 93%
“…To date, there is only a very limited number of studies that have focused on the effects of image size and its importance for diagnostic performance. [1][2][3][4][5] Interestingly, the results of these studies are mixed.…”
Section: Introductionmentioning
confidence: 99%